2017
DOI: 10.1051/matecconf/201710105005
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study on the effect of rainfall pattern to slope stability

Abstract: Abstract. Landslide in Indonesia usually occurs during the rainy seasons. Previous studies showed that rainfall infiltration has a great effect on the factor of safety (FS) of slopes. This research focused on the effect of rainfall pattern on the FS of unsaturated slope with different slope angle i.e.: 30°, 45°, and 60°. Three different rainfall patterns, which are normal, advanced, and delayed were considered in the analysis. The effects of low or high hydraulic conductivity of the soil are also observed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Hence, the development and the changes in the negative pore-water pressure were analysed using a method similar that has been used in the slope stability analysis by Perrone et al (2008). Moreover, several studies have stressed that pore-water pressures may also be affected by the different types of soils (; Rahimi et al, 2011 Sagitaningrum, andBahsan, 2017).…”
Section: Pore-water Pressurementioning
confidence: 99%
“…Hence, the development and the changes in the negative pore-water pressure were analysed using a method similar that has been used in the slope stability analysis by Perrone et al (2008). Moreover, several studies have stressed that pore-water pressures may also be affected by the different types of soils (; Rahimi et al, 2011 Sagitaningrum, andBahsan, 2017).…”
Section: Pore-water Pressurementioning
confidence: 99%
“…Rainfall-induced slope instability is usually related to slope type, gradient, soil properties, and rainfall intensity [15,16]. Controlling the gradients and types of slopes is one of the effective measures used to reduce rainfall damage [17,18], and the flatter the slope is, the higher the safety factor is during rainfall events [16]. For man-made dammed stockpiles, the flatter slope means less stockpile quantity within a certain range, and a reduction in slope gradient can harm the economic and social value of man-made stockpiles.…”
Section: 1 Introduction Of the Test Systemmentioning
confidence: 99%
“…Many studies have concluded that the higher the slope angle lower both the initial and minimum factors of safety [5,11,12]. In contrast, the reduction of the factor of safety in gentle slopes is higher than that of steeper slopes at heavy rainfall [13][14][15]. According to [5], under a short-term rainfall (i.e.…”
Section: Introductionmentioning
confidence: 99%